Shear Strength of a Crushed Sandstone-Mudstone Particle Mixture - Jun-Jie Wang; Zhen-Feng Qiu; Wen-Jie Deng (International Journal of Architectural Engineering Technology, 2014)
The present study focuses on the shear strength of a crushed sandstone-mudstone particle mixture. The mixture is widely used as a main filling material in many geotechnical engineering works. In order to investigate the shear strength of the mixture, triaxial tests under different confining pressures in laboratory are performed for 108 specimens with different dry densities and water contents. The dry density of the specimens ranges from 1.80 to 2.10 g/cm3, and the water content from 4.00 to 9.00 % and to saturation. In the tests, four confining pressures, which are 100, 200, 300 and 400 kPa, are applied. The testing results indicate that the angle of shearing resistance of the mixture in unsaturated state ranges from 16.90 to 32.98°. The angle of shearing resistance is generally decreasing with the increase of the confining pressure. With the increase of the dry density, the angle of shearing resistance increases. The angle is generally increasing then decreases as a parabola with the increase of the water content. The wetting may decrease the value of the angle about 0.4 to 2.7°.